ETNOBOTANIC AND ETNOVET IN JACU SETTLEMENT IN MUNICIPALITY OF POMBAL-PARAIBA - BRAZIL - Araújo, Francisco Almir de; Leite, Delzuite Teles; Sousa, Luci Cleide Farias Soares; Fernandes, Almair Albuquerque (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2012)
The current ethnobotanical studies record the use of medicinal plants as giving large awareness through models and empirical use of phototherapy between communities and their people. This research aimed to an ethnobotanical and ethnovet survey in the Jacu settlement in the municipality of Pombal - PB. In the survey, it was through the residents, the rescue register the use of the medicinal species usually used as well as its therapeutic use. It was administered a questionnaire to residents of the settlement addressing the general issues around the use of medicinal species, the interviews were conducted with 30 of the 40 families residing in the settlement, aged between 25 and 70 years, the questions were about plants use proven in people and animals. Information was collected between the months of January and February 2011. 40 have been classified as medicinal plants taken, and confirmation of its uses and effectiveness of all. The families of plants that most appeared were: Fabaceae, Verbenaceae, Capparaceae, and Asteraceae. The species of medicinal use are used throughout the year, requiring more research so that, using the same can be increasingly widespread especially with the population of settlements. Keywords: Popular Medicine, Phytotherapy, Healing substances.